Gaya Kepemimpinan Perempuan Terhadap Efektivitas Lembaga Kemahasiswaan Fakultas Ilmu Sosial Dan Hukum Di Universitas Negeri Makassar - Ahmad Maroddin; Muh Said; Ibrahim Ibrahim; Kasmawati Kasmawati (Social Landscape Journal, 2022)
This study was conducted with the aim of knowing: 1) Women's Leadership Style on the Effectiveness of Student Institutions at the Faculty of Social Sciences and Law at Makassar State University, 2) Factors that Determine Women's Leadership Style on the Effectiveness of Student Institutions, Faculty of Social Sciences and Law at Makassar State University. . The type of research used is descriptive qualitative. Data was collected by conducting observations, interviews, and documentation. Data analysis processing techniques go through four stages, namely: data collection, data reduction, data presentation, and drawing conclusions. Based on the results of the research, it is known that: 1) Women's Leadership Style on the Effectiveness of Student Institutions at the Faculty of Social Sciences and Law at Makassar State University, namely the traditional leadership style, namely being responsible, obeying the rules, nurturing and evaluating. The future leadership style is independent, innovative, and educative. The preferred leadership style is competent, influential and trustworthy. The delegation leadership style is responsible, independent, and competent. The sharing leadership style is open, understand the rules, dedicated. 2) Factors that Determine Women's Leadership Style on the Effectiveness of Student Institutions at the Faculty of Social Sciences and Law at Makassar State University, namely achieving goals, namely knowing targets, coordination, motivation. Organizational commitment is totality, consistency, trust. Efficiency, namely time management, forming a work team and implementation calendar, loyalty. Moral and cohesiveness are exemplary, nurturing, caring. Leadership abilities are influential, innovative, assertive and responsible.